Short selling and stock price crash risk - Chung, Jay M.; Wang, Shu Feng (Journal of Derivatives and Quantitative Studies, 2020)
This paper aims to investigate short selling and stock price crash risk. The authors find that short selling is positively associated with one-month-ahead stock price crash risk, consistent with the literature showing that short sellers are informed traders. The authors attribute this prediction ability to the information short sellers receive from foreign investors with high levels of ownership in a firm. The results shed light on policy issues regarding short selling regulation.
Keywords: Crash risk; Foreign ownership; Short selling